Design and Parametric Analysis of Compound Parabolic Concentrator for Photovoltaic Applications - Masood, F. (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper presents the design process and analyses the interrelationship amongst the critical design parameters of a low concentration Compound Parabolic Concentrator well suited for rooftop photovoltaic applications. The compound parabolic concentrator (CPC) is a non-imaging concentrator used to effectively concentrate solar radiation over a photovoltaic module to obtain a larger output with fewer PV cells. The CPC, intended for PV applications, was designed for an absorber width of78 mm and an acceptance half-angle of 200. A MATLAB code was developed to generate a CPC profile using design equations. The implications of diverse design parameters for CPC height, entry aperture width, and total mirror area were examined. The designed concentrator was then truncated to achieve material saving and avoid multiple reflections of incident rays to obtain better optical efficiency. The repercussions of truncating the upper portions of CPC were investigated to determine the optimum truncation position. The truncated CPC height for different truncation positions was compared with full height. The height and aperture width were computed for different acceptance half-angles and concentration ratios. The effect of PV absorber width on the entry aperture and total height was also analyzed. The interrelationship between optical concentration ratio and acceptance half-angle was demonstrated for various acceptance half-angles. The resulting two-dimensional geometry is best suited for PV applications. Â© 2021 IEEE.